Innate Immunity in the Middle Ear Mucosa - Massa, Helen M.; Spann, Kirsten M.; Cripps, Allan W. (Frontiers in Cellular and Infection Microbiology, 2021)
Otitis media (OM) encompasses a spectrum of clinical presentations ranging from the readily identifiable Acute OM (AOM), which is characterised by otalgia and fever, to chronic otitis media with effusion (COME) where impaired hearing due to middle ear effusion may be the only clinical symptom. Chronic suppurative OM (CSOM) presents as a more severe form of OM, involving perforation of the tympanic membrane. The pathogenesis of OM in these varied clinical presentations is unclear but activation of the innate inflammatory responses to viral and/or bacterial infection of the upper respiratory tract performs an integral role. This localised inflammatory response can persist even after pathogens are cleared from the middle ear, eustachian tubes and, in the case of respiratory viruses, even the nasal compartment. Children prone to OM may experience an over exuberant inflammatory response that underlies the development of chronic forms of OM and their sequelae, including hearing impairment. Treatments for chronic effusive forms of OM are limited, with current therapeutic guidelines recommending a “watch and wait” strategy rather than active treatment with antibiotics, corticosteroids or other anti-inflammatory drugs. Overall, there is a clear need for more targeted and effective treatments that either prevent or reduce the hyper-inflammatory response associated with chronic forms of OM. Improved treatment options rely upon an in-depth understanding of OM pathogenesis, particularly the role of the host innate immune response during acute OM. In this paper, we review the current literature regarding the innate immune response within the middle ear to bacterial and viral otopathogens alone, and as co-infections. This is an important consideration, as the role of respiratory viruses as primary pathogens in OM is not yet fully understood. Furthermore, increased reporting from PCR-based diagnostics, indicates that viral/bacterial co-infections in the middle ear are more common than bacterial infections alone. Increasingly, the mechanisms by which viral/bacterial co-infections may drive or maintain complex innate immune responses and inflammation during OM as a chronic response require investigation. Improved understanding of the pathogenesis of chronic OM, including host innate immune response within the middle ear is vital for development of improved diagnostic and treatment options for our children.